Study of thermo-physical properties, heat transfer and frictional loss of GNPS, NDG and rGO nanofluids in closed conduit flow / Emad Sadeghinezhad - Emad, Sadeghinezhad (2015)
Heat transfer fluids have inherently low thermal conductivity that greatly limits the heat exchange efficiency. While modification of surface materials, extension of surfaces, alternation of process parameters and redesigning heat exchange equipment to increase the heat transfer rate has reached a limit, many research activities have now focused on improvement of heat transfer liquid. Improvement of the thermal transport properties of the fluids by adding more thermally conductive solids into liquids has become a prominent research avenue. A nanofluid is recognized as the suspension of nanoparticles in a base fluid. Nanofluids are promising heat exchanger fluids for heat transfer enhancement due to their high thermal conductivity. Presently, discrepancy exists in nanofluid’s thermal conductivity data in the literature, and also the enhancement mechanisms have not been fully understood yet. Experimental studies are involved with the effects of some parameters such as particle concentration, particle size, and temperature on thermal conductivity. The major efforts given here are: to determine methods to characterize a nanoparticle colloid’s mass loading, chemical constituents, particle size, and pH; to determine temperature and loading dependent viscosity and thermal conductivity; to determine convective heat transfer coefficient and viscous pressure losses in a heated horizontal tube; and finally to determine the feasibility for potential use as enhanced performance heat exchanger fluid in energy transport systems. The thermal transport properties of nanofluids, including thermal conductivity, viscosity, heat capacity, contact angle, and electrical conductivity were characterized and modeled. In these nanofluid study the thermal conductivity of the nanofluids are observed higher than those of the base fluids. Forced convection research on nanofluids is important for practical application of nanofluids. The heat transfer coefficient was investigated experimentally in a flow loop with a horizontal tube test section subjected to constant heat flux at a various flow rate ranges. Initial experiments were conducted with pure water for validation of experimental data and accuracy. The experimental results, represented in Nusselt number (Nu) are compared to the classical Gnielinski, Petukhov and Dittus-Boelter equations. It was observed that Petukhov equation had shown less deviations and it is applicable in turbulent flow range for single phase fluid. For the recent experimental observations the heat transfer enhancement to nanofluids have exceeded the associated thermal conductivity enhancement, which might be explained by thermal dispersion, which occurs due to random motion of nanoparticles. Addition of the nanoparticles to the base fluid significantly increases their heat transfer coefficient compared to pure water as observed in this study. However, increasing of small amount of concentrations in the lower concentration range of this work has shown much effect on heat transfer enhancement. The ultimate goal is to contribute the understanding of the mechanisms of nanoparticle colloid behavior, as well as, to broaden the experimental database of these new heat transfer media. However, the present investigation results have upgraded the thermo-physical properties and heat transfer enhancement graphene family, where 200% increase of heat transfer coefficient and it is remarkable observation at low concentration of 0.1wt%. From this study it is observed that this types of nanofluids could be selected for the specific cases, where high heat transfer rate should be concern.